NATO Chief Admits NATO Expansion Was Key to Russian Invasion of Ukraine (Jeffrey D. Sachs, 2023)
The continuing U.S. obsession with NATO enlargement is profoundly irresponsible and hypocritical. And now Ukrainians are paying a terrible price.